RISK SHARING BETWEEN UNRESTRICTED-INVESTMENT-ACCOUNT-HOLDERS AND SHAREHOLDERS OF ISLAMIC BANKS: IMPLICATIONS ON STABILITY AND RESILIENCE - Ahmad Mohammad Barau; Saiful Azhar Rosly; Zulkarnain Mohammad Sori (Bank Indonesia, 2023)
The allocation of profit and loss to the unrestricted investment account holders (URIAHs) is a fundamental principle of Islamic banking where both the URIAHs and the Shareholders participate in funds mobilization through a risk-sharing arrangement. The study investigates the risk adjusted return received by both the unrestricted investment account holders and shareholders as well as the level of risk sharing between them for Islamic banks in Nigeria, Sudan, Bahrain and Qatar using financial ratio analysis, difference in mean t-test and Var-at-Risk (VaR) methodologies. The paper concludes that, contrary to the findings of many previous studies, the unrestricted investment account holders receive lower risk adjusted returns than the Shareholders do and at a higher risk in some of these countries and also the Central Banks impose a risk sharing value (the alpha factor) which is always different from the actual computed value of the risk sharing parameter for the banks and these are the likely potential sources of instability in the Islamic banks of these countries.